Umbelliferone Impedes Biofilm Formation and Virulence of Methicillin-Resistant Staphylococcus epidermidis via Impairment of Initial Attachment and Intercellular Adhesion - Swetha, Thirukannamangai Krishnan; Pooranachithra, Murugesan; Subramenium, Ganapathy Ashwinkumar; Divya, Velayutham; Balamurugan, Krishnaswamy; Pandian, Shunmugiah Karutha (Frontiers in Cellular and Infection Microbiology, 2019)
Staphylococcus epidermidis is an opportunistic human pathogen, which is involved in numerous nosocomial and implant associated infections. Biofilm formation is one of the prime virulence factors of S. epidermidis that supports its colonization on biotic and abiotic surfaces. The global dissemination of three lineages of S. epidermidis superbugs highlights its clinical significance and the imperative need to combat its pathogenicity. Thus, in the current study, the antibiofilm activity of umbelliferone (UMB), a natural product of the coumarin family, was assessed against methicillin-resistant S. epidermidis (MRSE). UMB exhibited significant antibiofilm activity (83%) at 500 μg/ml concentration without growth alteration. Microscopic analysis corroborated the antibiofilm potential of UMB and unveiled its potential to impair intercellular adhesion, which was reflected in auto-aggregation and solid phase adherence assays. Furthermore, real time PCR analysis revealed the reduced expression of adhesion encoding genes (icaD, atlE, aap, bhp, ebh, sdrG, and sdrF). Down regulation of agrA and reduced production of secreted hydrolases upon UMB treatment were speculated to hinder invasive lifestyle of MRSE. Additionally, UMB hindered slime synthesis and biofilm matrix components, which were believed to augment antibiotic susceptibility. In vivo assays using Caenorhabditis elegans divulged the non-toxic nature of UMB and validated the antibiofilm, antivirulence, and antiadherence properties of UMB observed in in vitro assays. Thus, UMB impairs MRSE biofilm by turning down the initial attachment and intercellular adhesion. Altogether, the obtained results suggest the potent antibiofilm activity of UMB and the feasibility of using it in clinical settings for combating S. epidermidis infections.